1982
DOI: 10.1002/oms.1210170503
|View full text |Cite
|
Sign up to set email alerts
|

The use of triple quadrupoles for sequential mass spectrometry: 1—The instrument parameters

Abstract: Triple quadrupoles are becoming widely used in sequential mass spectrometry. The observed spectra are very dependent upon the choice of instrument parameters such as the gas target density, the mode of operation of the central quadrupole, and the direct current levels of the quadrupoles (rod-offsets) which determine the collision energy and the maximum mass resohlfioIIL) in each d y i n g quadrupole. The influence of each of the instrument parameters is d m with examples of experimental measurements of perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(58 citation statements)
references
References 12 publications
1
57
0
Order By: Relevance
“…This concordance establishes 1) that our instrument is kinetically well behaved, and 2) the validity of Dawson's design considerations (closely-coupled quadrupole fields, properly filled acceptance, etc.) [3][4][5][6][7]. Similar agreement between Ln Y and Ln W measure- …”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This concordance establishes 1) that our instrument is kinetically well behaved, and 2) the validity of Dawson's design considerations (closely-coupled quadrupole fields, properly filled acceptance, etc.) [3][4][5][6][7]. Similar agreement between Ln Y and Ln W measure- …”
Section: Discussionmentioning
confidence: 64%
“…Letters of inquiry from prospective participants may be sent to NBS. [50] demonstrated that computer simulation of breakdown curves is plausible. Hence, one can envision a CAD spectral database of critically-evaluated cross sections U;j. Ui/(, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low energy CID was carried out in the second quadrupole with argon as the collision gas at a typical thickness [27,28] of approximately 2.0 × 1014 atoms cm 2 for the TAGA, and with nitrogen at a thickness of approximately 20 × 1014 molecules cm -2 for the API 300. The collision energy at the laboratory frame of reference (Ela b) was typically approximately 40-80 eV.…”
Section: Methodsmentioning
confidence: 99%